2013
DOI: 10.3109/07420528.2013.775144
|View full text |Cite
|
Sign up to set email alerts
|

Daylight saving time transitions and acute myocardial infarction

Abstract: Most recently, the possible impact of transitions to and from daylight saving time (DST) on the increased incidence of acute myocardial infarction (AMI) has been suggested. The goal of this report was to analyze independent influence of DST transitions on the incidence of AMI with simultaneous control for the confounding presence of situational triggers such as physical exertion, emotional stress, heavy meals, and sexual intercourse, as well as for other clinical factors. Detailed information was obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
1
35
3
Order By: Relevance
“…In contrast to Janszky et al [ 6 , 7 ] but in line with Culic [ 8 ] we found men to be more prone to the spring shift. This may be explained by the fact that men are more likely to be later chronotypes than women also in later adulthood [ 21 , 23 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to Janszky et al [ 6 , 7 ] but in line with Culic [ 8 ] we found men to be more prone to the spring shift. This may be explained by the fact that men are more likely to be later chronotypes than women also in later adulthood [ 21 , 23 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study from Croatia on 2,412 hospitalized AMI survivors confirmed the significant increase of AMI incidence for the first 4 workdays after spring transition with a particular excess on Monday [ 8 ]. In contrast to the Swedish results, the authors reported a significant increase after the autumn transition for the first four workdays with a peak on Tuesday and Thursday.…”
Section: Introductionmentioning
confidence: 93%
“…Among the 2633 retrieved papers, we identified seven studies (including >115,000 subjects) that met the selection criteria and were included in the analyses [17,18,19,20,21,22,23] (Figure 1). All were cohort studies, which retrospectively analysed data from national- or county-level disease registries [17,19,23], health insurance databases [21] or hospital discharge abstracts [18,20,22] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 2633 retrieved papers, we identified seven studies (including >115,000 subjects) that met the selection criteria and were included in the analyses [17,18,19,20,21,22,23] (Figure 1). All were cohort studies, which retrospectively analysed data from national- or county-level disease registries [17,19,23], health insurance databases [21] or hospital discharge abstracts [18,20,22] (Table 1). All studies were published from 2008 onwards (five after 2012 [17,18,20,21,22]); five were based in a European country (Sweden, Finland, Germany and Croatia) [17,18,19,20,23] and two in USA [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, other studies, the majority investigating risk of injuries or accidents following DST transitions, found no effects 23 28 31–33 or no difference in effects between shifts. 21 25 34 …”
Section: Introductionmentioning
confidence: 99%